2008
DOI: 10.1097/wnr.0b013e3282f2b4eb
|View full text |Cite
|
Sign up to set email alerts
|

Altered blood–brain barrier integrity in adult aquaporin-4 knockout mice

Abstract: To investigate the role of astroglial water channel aquaporin-4 (AQP4) in maintaining blood-brain barrier integrity, structure and permeability of the brain microvessels were investigated in adult AQP4 knockout mice. Altered ultrastructure of brain microvessels, including open tight junctions and swollen perivascular astrocytic endfeet, were frequently observed in the AQP4 null mice. Likewise, AQP4 deficiency significantly downregulated expression of glial fibrillary acidic protein in perivascular processes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
97
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 18 publications
4
97
1
2
Order By: Relevance
“…As AQP4 is known to regulate water fluxes in the brain, it was likely that this altered expression would influence BBB permeability. Accordingly, altered BBB integrity associated with hyperpermeability has been observed in AQP4 knockout mice (6). To directly test this hypothesis, we cultured HFAs and BBB-ECs on alternate sides of a Boyden chamber membrane and found that NMO-IgG-containing sera induce a significant increase in BBB permeability.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As AQP4 is known to regulate water fluxes in the brain, it was likely that this altered expression would influence BBB permeability. Accordingly, altered BBB integrity associated with hyperpermeability has been observed in AQP4 knockout mice (6). To directly test this hypothesis, we cultured HFAs and BBB-ECs on alternate sides of a Boyden chamber membrane and found that NMO-IgG-containing sera induce a significant increase in BBB permeability.…”
Section: Discussionmentioning
confidence: 98%
“…AQP4 is mainly expressed on astrocyte end-feet at the bloodbrain barrier (BBB) and brain-cerebrospinal fluid barrier (4). Analyses of AQP4-deficient mice revealed its involvement in cerebral water and ion homeostasis regulation, astrocyte migration, neural signal transduction, and demonstrated its role for the maintenance of BBB integrity (5,6).…”
mentioning
confidence: 99%
“…8 As AQP4 is highly concentrated in the area of the BBB, it is believed to have important roles in maintaining BBB integrity throughout development and in mature individuals. 9,10 Furthermore, our previous study shows that AQP4 deletion resulted in more serious disruption of BBB in morphology and function after ICH. 11 It has been reported that upregulation of AQP4 expression is observed in hypoxic-ischemic neonatal rats after receiving EPO.…”
mentioning
confidence: 97%
“…8 As AQP4 is highly concentrated in the area of the BBB, it is believed to have important roles in maintaining BBB integrity throughout development and in mature individuals. 9,10 …”
mentioning
confidence: 99%
“…Notably, these Aqp4 -/-animals are reported to show structural brain abnormalities, including altered BBB integrity (460). Such abnormalities are not in line with other studies on Aqp4 knockout animals (292,311,312).…”
Section: Selective Vulnerability Mediated By the Glial Microenvironmementioning
confidence: 55%